Buku Ilustrasi Tenun Pandai Sikek Untuk Melestarikan Budaya Minangkabau - Fajar Afif Putra; Dini Faisal (Institut Nalanda, 2023)
Songket from Pandai Sikek is one of the most famous Minangkabau woven products. Because of its beautiful motifs and colors, Pandai Sikek's songket weaving has many fans, both at home and abroad. The motifs used are motifs that have been owned for a long time and are hereditary motifs, but there are some motifs that have been lost due to the development of globalization. The flow of globalization and the rapid development of technology have shifted people's attention, especially the younger generation, to care about culture which has resulted in the waning of public interest and knowledge of Pandai Sikek weaving. Therefore a solution is needed by designing a media specifically for teenagers in the form of an illustrated book so that it can provide information and add insight about Pandai Sikek weaving. The design of this work uses the glassbox method with the design stages of preparation, incubation, lumination, and verification. In collecting data obtained from field observations, interviews reviewing literature obtained from various sources. From the results of writing, it is obtained that the media used in the design is in the form of illustrated books with supporting media tote bags, t-shirts, x-banners, pins, stickers, posters and key chains.